Fatores de sucesso do ambiente na formação esportiva de crianças: o caso de um projeto extensionista de basquetebol - Flach, Mônica Cristina (2024)
This study sought to analyze the environmental success factors of a Brazilian university outreach project focused on children's training through basketball. Ten professionals, fourteen children and sixteen family members participated in the research. For datacollection and analysis, document analysis and qualitative research techniques were employed: interviews, transcription,categorization and interpretation. The evidence revealed that financial conditions were sufficient for the project's development,highlighting the importance of the university and fundraising activities. Material conditions were deemed both satisfactory andunsatisfactory. The project's human resources included general and technical coordinators, volunteer teachers, monitors, interns, family members and children. The main activities in the sports training process were classes, festivals and meetings, while individual achievements included socialization, instilling social values, the creation of healthy habits, and fun. Donations of sneakers and uniforms to the children were part of the organizational culture. Commitment, interaction and principles expressed the espoused values, while fostering a love for basketball, increasing knowledge of the sport, and the training teachers and coaches were highlighted among the basic premises. In conclusion, the context portrays a successful environment which, by integrating itsresources, processes and results, has achieved success in the development of children through basketball.